Silver-oxide contact material with oxide continuous network and preparation method thereof
By using asymmetric MeO structural units to overlap in Ag-MeO contact materials to form a communication network and using the melting method to prepare a double-through structure, the problem of insufficient arc ablation resistance of existing materials is solved, and a higher Arc erosion resistance and processing performance.
Patent Information
- Application Number
- CN202411583926.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-18
AI Technical Summary
Among the existing Ag-MeO low-voltage contact materials, the diffuse structure material has insufficient resistance to arc ablation, resulting in increased contact resistance and material loss, which cannot meet the needs of high-rated current low-voltage switching appliances.
By overlapping the asymmetric MeO structural units to form a communication network, and combining with the permeability method, Ag-MeO contact material with double-through or double-connection structures is prepared to form a structure in which Ag and MeO are respectively connected, thereby improving the resistance to arc erosion. .
The connecting network is formed at low MeO content, which enhances the material's resistance to arc erosion, constrains splashing, maintains the material's processing performance, and improves production efficiency.
Smart Images

Figure HDA0005123840580000011 
Figure HDA0005123840580000012 
Figure HDA0005123840580000021
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of composite materials, and specifically relates to a silver-oxide (Ag-MeO) contact material with a continuous oxide network and a preparation method thereof, and more particularly to a silver-oxide contact material in which silver (Ag) and oxide (MeO) phases are interconnected and a preparation method thereof. Background Art
[0002] The development of smart distribution networks has put forward higher requirements for the service life, rated current and breaking capacity of low-voltage switchgear. Contacts are the core components of low-voltage switches. In the process of disconnecting the circuit, arcs will be generated between the contacts, causing significant ablation of the contact materials, causing material degradation, resulting in increased contact resistance and eventual failure.
[0003] Silver-oxide (Ag-MeO) composite materials are widely used as low-voltage switch contact materials, among which MeO types include tin oxide (SnO2), zinc oxide (ZnO), indium oxide (In2O3), etc. People usually use powder metallurgy or internal oxidation methods to prepare Ag-MeO materials, and the obtained material structure is nano- or micron-sized MeO particles dispersed in the Ag matrix. Because MeO particles are separated by Ag, MeO particles will form a molten pool on the surface under arc ablation and flow freely, and it is easy to enrich the material surface to form a MeO layer, resulting in an increase in contact resistance; in addition, the molten Ag in the molten pool will splash under the action of arc impact, electric field force, steam pressure, etc., causing material loss. Such dispersed structure materials are severely ablated when breaking large currents, have low electrical life, and cannot meet the needs of large rated current low-voltage switch electrical appliances.
[0004] In the study of low-voltage and high-current switches, it was found that when the second phase in the contact material forms a connected skeleton, the material's arc erosion resistance can be effectively improved. For example, in the common Ag-W material used for high current, W forms a connected skeleton. After the arc melts the surface to form a molten pool, the W skeleton can be "rooted" in the solid matrix as a whole, thus avoiding the problem of enrichment on the surface; at the same time, the skeleton can effectively divide the molten pool, hinder the propagation of disturbances in the molten pool, inhibit the splashing of molten silver under the action of the arc, and improve the material's arc erosion resistance. However, in the Ag-MeO material, in order to take into account the requirements of hardness and processing performance, the MeO content is below 20wt.%, and the nearly spherical particles are difficult to accumulate to form a continuous network at such a low volume fraction; therefore, how to form a second phase connected skeleton at a low mass fraction while making the skeleton have good plasticity is a difficult engineering problem to solve. Summary of the invention
[0005] In order to overcome the problem of insufficient arc erosion resistance of the dispersed tissue material in the existing Ag-MeO low-voltage contact material, and the problem of resistance increase and material loss caused by arc erosion, the present invention proposes to use asymmetric MeO structural units to overlap to form a connected network, and combine the infiltration method to prepare Ag-MeO contact materials with double penetration or double connection structures. By using the characteristics of low penetration threshold of asymmetric units, a connected network is formed at low MeO content, and the arc erosion resistance is improved, so that the silver-oxide contact material uses the continuous oxide network to constrain the splashing; at the same time, because the structural units form a whole through friction and entanglement, they have plastic deformation ability, thereby maintaining the processing performance of the material and greatly improving production efficiency.
[0006] In order to achieve the above object, the present invention proposes the following technical solutions:
[0007] According to one aspect of the present invention, there is provided a silver-oxide contact material, comprising silver Ag and oxide MeO, wherein the content of the oxide is 1-20 wt % based on the total weight of the contact material, and the two phases of silver Ag and oxide MeO are interconnected, wherein the MeO phase is stacked in one-dimensional (wire) and / or two-dimensional (sheet) asymmetric units to form a continuous skeleton, and the Ag phase is filled in the MeO skeleton to form a dual-interconnected structure of the Ag and MeO phases.
[0008] The asymmetric MeO structural units are stacked to form a connected and flexible skeleton, and then the Ag phase is melted and infiltrated into the MeO skeleton to form a double-penetrating structure of Ag-MeO. Under arc ablation, the connected MeO skeleton can take root in the solid matrix, preventing MeO from enriching on the surface of the material, while restricting the splashing of molten silver and enhancing the material's resistance to arc erosion.
[0009] According to an embodiment of the present invention, the oxide MeO includes tin oxide (SnO2), zinc oxide (ZnO), and indium oxide (In2O3), and in particular, may be one or more selected from tin oxide (SnO2), zinc oxide (ZnO), and indium oxide (In2O3).
[0010] Those skilled in the art should understand that, in the present invention, MeO represents an oxide of metal Me, and the number of O therein will change according to the valence state of metal Me to satisfy the chemical valence balance.
[0011] According to an embodiment of the present invention, the oxide MeO phase asymmetric unit is a micro / nano structure. For example, in some embodiments, for a one-dimensional wire, its diameter is less than 2 μm (the thinnest diameter can reach 100 nm), the aspect ratio is greater than 10, and the length is greater than 20 μm; in some embodiments, for a two-dimensional sheet, its thickness is less than 2 μm, and the surface area is greater than 100 μm. 2 above.
[0012] According to an embodiment of the present invention, the content of the oxide may be 3-18%, such as 15%, 12%, 10%, 8% or 5%, based on the total weight of the contact material.
[0013] According to an embodiment of the present invention, based on the total weight of the contact material, the contact material also contains 0.5-5wt% (for example, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5%) of one or more wetting agents selected from copper oxide (CuO), lanthanum oxide (La2O3), tungsten oxide (WO3), and bismuth oxide (Bi2O3) to improve the wettability of the Ag phase and the MeO phase.
[0014] According to another aspect of the present invention, there is provided a method for preparing the above-mentioned silver-oxide contact material, the method comprising:
[0015] S1, preparation of MeO asymmetric unit;
[0016] S2, forming a MeO stacking network structure with the MeO asymmetric unit prepared in step S1;
[0017] S3, silver is infiltrated into the network structure of MeO stacking by melt infiltration method to prepare Ag-MeO contact material.
[0018] According to the present invention, in S1, the MeO asymmetric unit can be prepared by flame synthesis (flame melting method), hydrothermal synthesis, electrospinning and the like.
[0019] In one embodiment, in S1, it includes:
[0020] S1-1, metal Me (such as Zn) powder and polyvinyl butyral powder are mixed in a mass ratio of 0.05-3:1, and then the mixed powder is placed in an oxygen-containing environment in a furnace preheated to 400-1200°C, such as 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, and burned to produce MeO (such as ZnO) micron wires and / or sheets, wherein the particle size of the metal Me (such as Zn) powder can be 1-500μm, such as 5μm, 10μm, 50μm, 100μm, 200μm, 300μm, or 400μm.
[0021] In another embodiment, in S1, it includes:
[0022] S1-1', dissolving a chloride (such as tin chloride) or a nitrate (such as tin nitrate) of metal Me in a mixed solution of oleic acid and oleamine in a volume ratio of (5-10):1 to achieve a metal Me ion concentration of 0.01-0.5 mol / L, such as 0.02 mol / L, 0.05 mol / L, 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, and ultrasonicating, oscillating, and stirring until a uniform first solution is obtained; then, a second solution of deionized water and ethanol mixed in a volume ratio of 1:(5-10) equivalent to 40%-50% of the first solution is added dropwise to the first solution, and then the obtained mixed solution is charged into a hydrothermal reactor for hydrothermal reaction, such as heating at 150-200°C for 2-10 hours to obtain MeO (such as SnO2) micro / nanowires.
[0023] In yet another embodiment, in S1, it includes:
[0024] S1-1", a chloride (such as stannous chloride) or a nitrate (such as stannous nitrate) of metal Me is dissolved in ethanol to obtain a precursor solution A with a concentration of 0.1-0.2 g / mL, polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene oxide or polyvinyl acetate (average molecular weight of 10000-1000000) is dissolved in N,N-dimethylformamide to obtain a precursor solution B with a concentration of 0.1-0.2 g / mL, and the precursor solutions A and B are ultrasonicated, vibrated and stirred respectively until a uniform solution is obtained; then the precursor solutions A and B are mixed The mixture is combined and stirred until uniform, with the mass ratio of precursor solution A: precursor solution B being 0.8-2:1; the obtained mixed solution is then subjected to electrostatic spinning, for example, wherein the positive electrode voltage may be 10-18 kV, the negative electrode voltage is greater than -5 kV, and the positive and negative electrode spacing is 10-30 cm, to obtain MeO precursor fibers; the collected MeO precursor fibers are calcined in air at a temperature above 400° C. (for example, 500, 600, 700° C.) for more than 30 minutes (for example, 40, 50 or 60 minutes) to obtain MeO (for example, SnO2) fibers.
[0025] According to the present invention, in S2, the MeO asymmetric unit prepared in step S1 can be formed into a MeO stacked network structure, such as a block (columnar block) or a cake, by a pressing method (such as a molding method), a filtration method or a freeze-drying method.
[0026] Those skilled in the art will appreciate that when the suction filtration method or freeze-drying method is used, the solvent or dispersant used is a solvent or dispersant that does not react with MeO.
[0027] In one embodiment, in S2, the density (relative density) of the obtained network structure may be 2%-30%, for example, 3%, 6%, 9%, 12%, 15%, 18%, 21%, 24%, 27%, 30%, etc.
[0028] According to the present invention, if a wetting agent is present, the wetting agent can be blended with the asymmetric MeO or with Ag.
[0029] According to the present invention, if a wetting agent is present, in S2, in some embodiments, when a pressing method is used to form a MeO stacked network structure, the MeO asymmetric unit may be first pressed into a block (such as a columnar block), and then the wetting agent (powder) may be placed on the MeO block or pressed on the MeO block; or the wetting agent and the MeO asymmetric unit may be mixed and then pressed together to form a desired MeO stacked network structure, such as a block; when a filtration method or a freeze-drying method is used to form a MeO stacked network structure, the wetting agent and the MeO asymmetric unit may be dispersed and mixed with a dispersant (such as water), and then filtered or frozen to form a MeO stacked network structure, such as a cake or a block.
[0030] According to the present invention, in S3, silver is placed on or embedded in the MeO stacked network structure formed in step S2, and the temperature is increased to melt the silver for infiltration.
[0031] In one embodiment, in S3, the steps include: embedding the MeO stacked network structure (block) formed in step S2 with silver powder, or making the silver powder into blocks (such as pressing into columnar blocks), placing the silver blocks on the MeO stacked network structure formed in S2, and if there is an infiltrant, placing them on the side of the MeO stacked network structure having the infiltrant, heating (for example, above the melting point of silver, or above the eutectic point temperature of silver and the infiltrant, such as 1000°C) to melt the silver, and if there is an infiltrant, melting the silver together with the infiltrant and infiltrating into the MeO stacked network structure formed in S2, wherein the size of the silver block may be less than, equal to, or greater than the MeO stacked network structure formed in S2.
[0032] In one embodiment, if an infiltrant is present, S3 includes: embedding the block formed in step S2 with a mixed powder of silver and the infiltrant, or mixing silver powder and the infiltrant powder into a block (such as pressing into a columnar block), placing the block on the MeO stacked network structure formed in S2, and heating (for example, a temperature above the eutectic point of silver and the infiltrant, such as 1000°C) to melt the silver and the infiltrant and infiltrate into the MeO stacked network structure formed in S2, wherein the size of the silver block can be smaller than, equal to, or larger than the MeO stacked network structure formed in S2.
[0033] In one embodiment, a method for preparing a silver-oxide contact material having a dual through-hole structure with low oxide content is provided, comprising:
[0034] (1) First, a ZnO network composed of micro / nano wires and sheets is prepared: a ZnO asymmetric unit is prepared by flame transport synthesis, including mixing zinc (Zn) powder and polyvinyl butyral powder in a mass ratio of 0.05-3:1, then burning the mixed powder in a furnace at 400-1200° C. in an oxygen-containing environment to produce ZnO micro / nano wires and sheets, wherein the Zn powder has a particle size of 1-500 μm, and molding the obtained ZnO micro / nano wires and sheets to obtain a ZnO network structure (block skeleton, for example, such as Figure 1 or dispersing the obtained ZnO micro / nano wires and sheets into a solvent, and obtaining a ZnO network structure by suction filtration or freeze drying (for example, Figure 1 The structure shown), wherein the solvent is any solvent that does not react with ZnO;
[0035] (2) preparing a silver-zinc oxide (Ag-ZnO) contact material containing a ZnO micro-nano structure by a melt infiltration method: uniformly covering the top of the ZnO network structure with CuO powder, pressurizing to form a ZnO compact with the top covered with CuO, and pressing silver powder into a compact, placing the silver compact on the ZnO compact with the top covered with CuO, or mixing silver powder with CuO powder and pressing the compact, placing the Ag-CuO compact on the ZnO network structure (skeleton) in an air environment, and heating to a temperature above the Ag-CuO eutectic point (for example, heating to 1000°C for 30 minutes, with a heating and cooling rate of 10°C / min), and a Ag-ZnO material with a double-penetrating structure was prepared by a melt infiltration method, wherein the mass ratio of CuO:Ag is 0.005-0.05:1, for example, 0.01:1, 0.015:1, 0.02:1, 0.025:1, 0.03:1, and the mass ratio of ZnO:Ag is 0.01-0.25:1, for example, 0.03:1, 0.05:1, 0.1:1, 0.15:1, 0.2:1.
[0036] In one embodiment, a method for preparing a silver-oxide contact material having a dual through-hole structure with low oxide content is provided, comprising:
[0037] (1) First, SnO2 nanowires are prepared: 0.2-1 parts by weight of tin chloride is dissolved in a mixture of oleic acid and oleamine in a volume ratio of (5-10):1 to achieve a metal Sn ion concentration of 0.01-0.5 mol / L, and ultrasonic, oscillate, and stir for more than 2 hours until a uniform first solution is obtained; then a second solution of deionized water and ethanol mixed in a volume ratio of 1:(5-10) equivalent to 40%-50% of the first solution is added dropwise to the first solution, and then the mixed solution is charged into a hydrothermal reactor and heated at 150-200°C for 2-10 hours (for example, at 180°C for 3 hours) to obtain SnO2 micro / nanowires; the obtained powder (SnO2 micro / nanowires) and optional Bi2O3 powder are dispersed in a solvent or dispersant (such as deionized water), and a SnO2 network structure is obtained by suction filtration or freeze drying;
[0038] (2) Prepare a silver-tin oxide (Ag-SnO2) contact material containing SnO2 micro-nanostructure by melt infiltration: Place a silver-bismuth oxide block on a SnO2 network structure (skeleton) in an air environment, or place a silver block on a SnO2 network structure (skeleton) containing bismuth oxide, heat to a temperature above the Ag-Bi2O3 eutectic point (for example, heat to 1000°C and keep warm for 30 minutes, with a heating rate of 10°C / min), and use The infiltration method is used to prepare Ag-SnO2 material with a double-penetrating structure, wherein the mass ratio of Bi2O3:Ag is 0.005-0.05:1, for example, 0.01:1, 0.015:1, 0.02:1, 0.025:1, 0.03:1, and the mass ratio of SnO2:Ag is 0.01-0.25:1, for example, 0.03:1, 0.05:1, 0.1:1, 0.15:1, 0.2:1.
[0039] In one embodiment, a method for preparing a silver-oxide contact material having a low oxide content double-penetrating structure is provided, comprising: (1) first preparing SnO2 nanowires: dissolving stannous chloride in ethanol to obtain a precursor solution A with a concentration of 0.1-0.2 g / mL, dissolving polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene oxide or polyvinyl acetate (average molecular weight of 10000-1000000) in N,N-dimethylformamide to obtain a precursor solution B with a concentration of 0.1-0.2 g / mL, ultrasonicating, oscillating and stirring the A and B solutions for more than 3 hours to obtain a uniform solution; then mixing the A and B solutions and stirring until uniform, the precursor solution A: precursor solution B mass ratio is 0.8-2:1; then the obtained mixed solution is subjected to electrostatic spinning, wherein the positive electrode voltage is 10-18kV, the negative electrode voltage is greater than -5kV, and the distance between the positive and negative electrodes is 10-30cm, to obtain SnO2 precursor fibers; the collected SnO2 precursor fibers are calcined in air at a temperature above 400°C (for example, 500, 600, 700°C) for more than 30 minutes (for example, 40, 50 or 60 minutes) to obtain SnO2 fibers; the calcined SnO2 fibers and optional La2O3 powder are dispersed in a solvent or dispersant (such as deionized water), and a SnO2 network structure is obtained by suction filtration or freeze drying;
[0040] (2) Prepare Ag-SnO2 contact materials containing SnO2 micro-nano structures by melt infiltration: Place a silver-lanthanum oxide block on a SnO2 skeleton, or place a silver block on a SnO2 network structure (skeleton) containing lanthanum oxide in an air environment, heat to a temperature above the Ag-La2O3 eutectic point (for example, heat to 1000°C and keep warm for 30 minutes, with a heating and cooling rate of 10°C / min), and prepare Ag-SnO2 material with a double-through structure by melt infiltration, wherein the mass ratio of La2O3:Ag is 0.005-0.05:1, for example, 0.01:1, 0.015:1, 0.02:1, 0.025:1, 0.03:1, and the mass ratio of SnO2:Ag is 0.01-0.25:1, for example, 0.03:1, 0.05:1, 0.1:1, 0.15:1, 0.2:1.
[0041] In one embodiment, a method for preparing a silver-oxide contact material having a low oxide content double-penetrating structure is provided, comprising: (1) first preparing SnO2 micro / nanowires: placing Sn powder (e.g., 2 g) in a tube furnace, and keeping the temperature between 600-1200° C. for more than 20 min (e.g., 30, 40, 50 or 60 min) in an environment containing oxygen (1-100 sccm), and agglomeration of SnO2 nanowires will be generated in the tube furnace; pressing the obtained SnO2 wires with a mold to obtain a bulk skeleton with a density of 3-30%;
[0042] (2) Prepare Ag-SnO2 contact materials containing SnO2 micro-nano structures by melt infiltration: Place a silver-tungsten oxide (Ag-WO3) block on a SnO2 skeleton in an air environment, heat it to a temperature above the Ag-WO3 eutectic point, and prepare an Ag-SnO2 material with a double-penetrating structure by melt infiltration, wherein the mass ratio of WO3:Ag is 0.005-0.05:1, for example, 0.01:1, 0.015:1, 0.02:1, 0.025:1, 0.03:1, and the mass ratio of SnO2:Ag is 0.01-0.25:1, for example, 0.03:1, 0.05:1, 0.1:1, 0.15:1, 0.2:1.
[0043] The method used in the present invention is significantly different from the powder metallurgy combined with large plastic processing deformation of traditional materials in the past (Chinese patent document CN 102031408 A), and its essential difference is: first, the asymmetric MeO units are stacked into a skeleton and then filled with Ag, so as to ensure that the MeO phase in the material forms a through network; and the powder metallurgy method is used to prepare the material of fibrous MeO structure, firstly, the Ag powder is mixed and ball-milled with the MeO powder to obtain a composite powder in which the MeO particles are embedded in the Ag powder, and then the forming and drawing are performed, which separates the MeO particles by Ag, and the MeO phases are discontinuous. At the same time, in the method of the present invention, since the MeO skeleton is formed by friction and entanglement between asymmetric units, it has better deformation ability than the network obtained by sintering particles, thereby improving the plasticity and processing performance of the contact material. The contact material of this structure of the present invention utilizes the characteristics of asymmetric units with low penetration threshold to form a connected network at low MeO content. The continuous MeO skeleton can effectively restrain the splashing of Ag droplets under arc ablation, reduce the thickness of the ablation layer, and effectively enhance the arc erosion resistance. At the same time, the MeO skeleton is formed by stacking asymmetric units. Compared with the "hard connection" bonded by sintering in previous materials, it can withstand large strains without causing brittle fracture. Therefore, the material maintains good plastic processing properties, matches the plastic processing technology of the existing Ag contact material production process, and greatly improves production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 Shown are the actual macroscopic photographs (i.e., the embedded small figure in figure a)) of the asymmetric ZnO unit-joined precursor (i.e., ZnO compact) prepared in Example 1 of the present invention and its microscopic morphology (SEM images, a) and b)).
[0045] Figure 2The filter block prepared in Example 2 of the present invention, i.e., a real macroscopic photograph (i.e., the embedded small picture in figure a)) and a microstructure picture (SEM picture, a) and b)) of a block of entangled and stacked SnO2 nanowires are shown, showing that the SnO2 microwires and nanowires are entangled and overlapped to form a flexible SnO2 ceramic skeleton.
[0046] Figure 3 A schematic diagram showing a method for placing materials before infiltration according to an embodiment of the present invention.
[0047] Figure 4 The microstructure of Ag-ZnO obtained by infiltration in Example 1 is shown (SEM image).
[0048] Figure 5 The micrograph (SEM image) of the cross section of the double-penetrating Ag-ZnO material in Example 1 of the present invention and the Ag-ZnO material with the same composition and dispersed structure (Comparative Example 1) after ablation during 220V, 10A, 30,000 AC interruptions is shown.
[0049] Figure 6 The figure shows the comparison of mass loss of the double-penetrating Ag-ZnO material in Example 1 of the present invention and the Ag-ZnO material with the same composition and dispersed structure (Comparative Example 1) during 220V, 10A, and 30,000 AC interruptions. DETAILED DESCRIPTION
[0050] The following examples are only listed as examples of embodiments of the present invention and do not constitute any limitation to the present invention. It can be understood by those skilled in the art that modifications within the scope of the essence and concept of the present invention fall within the scope of protection of the present invention. Unless otherwise specified, the reagents and instruments used in the following examples are all commercially available products.
[0051] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0052] Unless otherwise specified, the reagents and materials used in the present invention are reagents and materials that are conventionally available (commercially available) in the art, and the methods and equipment used are methods and equipment conventionally used in the art.
[0053] Example 1
[0054] Preparation of Ag-ZnO based on flame synthesis
[0055] S1, Preparation of ZnO asymmetric unit (nanostructure)
[0056] Step 1: Place 50g of Zn powder and 50g of PVB (polyvinyl butyral) powder in a planetary ball mill, and use ceramic balls as the medium to perform ball milling. The ball milling speed is 200 rpm, the ball milling time is 2 hours, and the ball-to-material ratio is 10:1.
[0057] Step 2: Weigh 20 g of the Zn-PVB mixed powder obtained in the first step and put it into a 50 mL corundum crucible for flame combustion synthesis.
[0058] Step 3: Heat the tube furnace to 1000°C. The tube furnace uses an alumina tube with a length of 1m and an inner diameter of 5cm. One side of the tube furnace is connected to the gas line, and compressed air is introduced at a flow rate of 10mL / min to provide the oxygen required in the reaction process. The other side remains open for the introduction of reactants.
[0059] Step 4: Use tongs to quickly insert the crucible containing the mixed powder prepared in step 2 into the tube furnace that has been in a heat preservation state in step 3, and insert the crucible into the constant temperature zone of the tube furnace. The mixed powder will heat up quickly and start to burn with sufficient oxygen supply. The combustion of Zn powder will produce bright flames, and the combustion of PVB will produce black smoke and cause violent disturbances in the airflow. The flame and black smoke will be ejected from the open end of the tube furnace for about 1 minute. White ZnO products will be produced during the combustion process and carried to the low temperature area of the tube furnace by the airflow. The timing is started at the beginning of combustion, and the reaction time is 30 minutes to ensure the complete oxidation of Zn powder and the formation of nanostructures.
[0060] Step 5: Use tongs to take the ZnO produced in the fourth step out of the tube furnace for cooling, and take out the corundum crucible at the same time. It is found that the powder in the crucible has disappeared, and the product is fluffy white flocs, which are agglomerates produced by stacking and entanglement of nanostructured ZnO, with a density of about 3%. The previous four steps can be repeated to continuously produce sufficient ZnO.
[0061] S2, forming a ZnO stacked network structure by forming the ZnO nanostructures prepared above
[0062] Step 6: After the flocculent ZnO taken out in step 5 is cooled, weigh 10g of flocculent ZnO and put it into a φ20mm cold pressing mold, and apply pressure to make the height of the pressed block 31.6mm (corresponding to a density of 18%). Then release the pressure, take out the upper pressure head, and keep the lower pressure head and the pressed block in the lower mold. Figure 1 Shown are the actual macroscopic photographs of the prepared ZnO compact, i.e. the inset small image in figure a), and its microscopic morphology photographed by SEM (a) and b) in the figure).
[0063] Step 7: Pour 1.5 g of CuO powder into the mold opened in step 6, and vibrate the mold slightly so that the CuO powder evenly covers the top of the ZnO compact. Then insert the pressing head into the mold and press again to compress the height of the block to 31.6 mm. Then demold and remove the ZnO compact covered with CuO on the top.
[0064] S3, using melt infiltration method to infiltrate silver into the ZnO stacking network structure to prepare Ag-ZnO contact material
[0065] Step 8: Cold press 88.5g of Ag powder into a φ15mm columnar block (density above 50%) and place it on the ZnO block demolded in step 7, where the Ag block should be placed on the CuO-covered side. Since the ZnO block has sufficient strength, it can support the weight of the Ag block.
[0066] Step 9: Select Al2O3 powder with a particle size of more than 1μm and pad it on the bottom of the corundum crucible. Place the Ag block-ZnO block stacked in step 8 on the Al2O3 powder. Transfer the crucible containing the sample to a muffle furnace, heat it to 1000℃ at a heating rate of 10℃ / min in an air environment, keep it warm for 30 minutes for infiltration, and then cool it down to room temperature at a rate of 10℃ / min with the furnace.
[0067] Step 10: Grind the upper and lower surfaces of the composite material obtained after cooling in step 9 with 200-mesh sandpaper to remove oxide impurities adhering to the upper and lower surfaces, and obtain a double-penetrating structure Ag-ZnO material.
[0068] Example 2
[0069] Preparation of Ag-SnO2 based on chemical synthesis of SnO2
[0070] S1, Preparation of SnO2 asymmetric unit (micro / nanowire)
[0071] Step 1: Dissolve 10 g of tin chloride in a mixed solution of 200 mL of oleic acid and 25 mL of oleamine, and perform ultrasonication, oscillation, and stirring for more than 2 hours until a uniform solution is obtained.
[0072] Step 2: Add a mixed solution of 10 mL of deionized water and 100 mL of ethanol dropwise into the solution obtained in step 1. Then, the mixed solution is placed in a hydrothermal reactor, heated at 180°C for 3 hours, and then cooled to room temperature to obtain SnO2 micro / nanowires.
[0073] Step 3: Filter the solution in the reactor of step 2, and disperse it in deionized water again, stir and wash it by ultrasound, and repeat the filtering-washing process twice. The above steps can be repeated to obtain enough SnO2 micro / nanowires.
[0074] S2, forming a SnO2 stacked network structure by forming the SnO2 micro / nanowires prepared above
[0075] Step 4: Disperse 10 g of SnO2 powder and 1.5 g of Bi2O3 powder washed in step 3 in deionized water, filter the dispersion through a φ10 mm filter paper, and the resulting filter block is a block of entangled and stacked SnO2 micro / nanowires, the density of which is determined by the aspect ratio of the particles and is approximately 27%. Figure 2 Shown are the actual macroscopic photograph of the prepared filter block, i.e., a block of entangled and stacked SnO2 nanowires, i.e., the embedded small picture in figure a), and its microstructure image taken by SEM, i.e., a) and b) in the figure, which show that the SnO2 microwires and nanowires are entangled and overlapped to form a flexible SnO2 ceramic skeleton.
[0076] S3, using the melt infiltration method to infiltrate silver into the SnO2 stacked network structure to prepare Ag-SnO2 contact material
[0077] Step 5: 88.5 g of Ag powder was cold pressed into a φ8 mm cylindrical block and placed on the filter block obtained in step 4. Since the SnO2 block has sufficient strength, it can support the weight of the Ag block.
[0078] Step 6: Select Al2O3 powder with a particle size of more than 1μm and pad it at the bottom of the corundum crucible. Place the Ag block-SnO2 block stacked in step 5 on the Al2O3 powder. Transfer the crucible containing the sample to a muffle furnace, heat it to 1000℃ at a heating rate of 10℃ / min in an air environment, keep it warm for 30 minutes for infiltration, and then cool it down to room temperature at a rate of 10℃ / min.
[0079] Step 7: Grind the upper and lower surfaces of the composite material obtained after cooling in step 8 with 200-mesh sandpaper to remove oxide impurities adhering to the upper and lower surfaces, and obtain a double-penetrating structure Ag-SnO2 material.
[0080] Example 3
[0081] S1, Preparation of SnO2 asymmetric unit (fiber)
[0082] Step 1: Dissolve 10 g of stannous chloride in 100 mL of ethanol solution, stir and sonicate for more than 3 hours to obtain a uniform precursor solution A.
[0083] Step 2: Dissolve 10 g of polyvinyl acetate (PVAc, average molecular weight 10000-1000000) in 100 mL of N,N-dimethylformamide (DMF), stir and ultrasonicate for more than 3 hours to obtain a uniform precursor solution B.
[0084] Step 3: Mix the A and B solutions in the first and second steps in a mass ratio of 1:1 to initiate hydrolysis, and let the hydrolysis stand for 4 hours.
[0085] Step 4: Electrospin the solution after the hydrolysis in step 3, extract 10mL of the hydrolysis solution, and use a metal needle with a diameter of 420μm. The injection end of the solution is the positive electrode, the voltage is 15kV; the aluminum foil is used as the receiving end to connect the negative electrode, the voltage is -5kV; the distance between the positive and negative electrodes is 20cm; spin until all the solution is used up.
[0086] Step 5: Place the SnO2 precursor fibers collected from the negative electrode in step 4 into a corundum crucible and transfer to a muffle furnace for heat treatment. The heating rate is 5°C / min, and after heating to 400°C, keep the temperature for 60 minutes, and then cool with the furnace at a rate of 10°C / min. The SnO2 precursor fibers are transformed into SnO2 fibers. Steps 1 to 5 can be repeated to obtain enough SnO2 fibers.
[0087] S2, the SnO2 fibers prepared above are formed into a SnO2 stacked network structure
[0088] Step 6: Take 3 g of the SnO2 fiber obtained in the fifth step, add it to 1 L of deionized water, and use an IKA T25 disperser to disperse it at a speed of 20,000 rpm for 2 hours to obtain a dispersion.
[0089] Step 7: Add 0.5g La2O3 powder (particle size <10μm) to the dispersion in step 6, and filter the dispersion through a φ10mm filter cup. The resulting filter block is a block of entangled and stacked SnO2 nanowires. A φ10mm resin cylinder is selected as the upper pressure head, and the filter block is extended from the filter cup to compress the filter block, so that the height of the filter block is 25.8mm (density is about 4.5%).
[0090] S3, using the melt infiltration method to infiltrate silver into the SnO2 stacked network structure to prepare Ag-SnO2 contact material
[0091] Step 8: Cold press 96.5g of Ag powder into a φ8mm cylindrical block and place it on the filter block obtained in step 7. Since the SnO2 block has sufficient strength, it can support the weight of the Ag block.
[0092] Step 9: Select Al2O3 powder with a particle size of more than 1μm and pad it at the bottom of the corundum crucible. Place the Ag block-SnO2 block stacked in step 8 on the Al2O3 powder. Transfer the crucible containing the sample to a muffle furnace, heat it to 1000℃ at a heating rate of 10℃ / min in an air environment, keep it warm for 30 minutes for infiltration, and then cool it down to room temperature at a rate of 10℃ / min.
[0093] Step 10: Grind the upper and lower surfaces of the composite material obtained after cooling in step 9 with 200-mesh sandpaper to remove oxide impurities adhering to the upper and lower surfaces, and obtain a double-penetrating structure Ag-SnO2 material.
[0094] Figure 1 , Figure 2 The actual macroscopic photographs and microstructural diagrams of the asymmetric units prepared in Examples 1 and 2 of the present invention are shown respectively. Figure 1 , Figure 2 The Ag-MeO double through-contact material based on asymmetric structural units of the present invention has a microstructure different from the typical microstructure of the traditional Ag-MeO material in which the MeO phase is dispersed in the Ag matrix. The Ag and MeO phases each form a through-contact network, and the MeO content is less than 20wt.%, thereby realizing a double through-contact network structure with a low MeO content.
[0095] Comparative Example 1
[0096] Silver powder, zinc oxide powder (diameter 100nm-1μm), and copper oxide powder (diameter 50nm-1μm) were mixed in the same amount as in Example 1, and the mixed powder was ball-milled with tungsten carbide balls in a planetary ball mill for 12h (ball-to-material weight ratio 10:1), and the ball-milled powder was annealed in a muffle furnace at 400°C for more than 2h. The annealed powder was cold-pressed at a pressure of more than 300MPa, and then the compact was heated to 930°C in a muffle furnace and sintered for 2h (wherein the heating and cooling rate was 10°C / min), and then hot-pressed at 900°C and a pressure of more than 30MPa in a hot pressing furnace for more than 1h (wherein the heating and cooling rate was 10°C / min), to obtain a dense comparative material with a dispersed structure.
[0097] The materials of Example 1 and Comparative Example 1 were respectively made into low-voltage switches, and ablation and mass loss tests were performed according to "GB / T 24273-2009 Test Methods for Electrical Properties of Electrical Contact Materials". The results are shown in Figure 5 and Figure 6 middle.
[0098] Figure 5 The cross-sectional micrographs of two materials with different microstructures after ablation during 220V, 10A, 30,000 AC interruptions are shown, wherein the penetration depth of the holes in the double-penetrating Ag-ZnO material of Example 1 is ~30μm, and the penetration depth of the holes in the particle-dispersed Ag-ZnO material of Comparative Example 1 reaches ~200μm.
[0099] Depend on Figure 6 It can be seen that under the same composition, the mass loss of the double-penetrating Ag-ZnO material of Example 1 with a network structure is reduced by ~30% compared with the particle dispersed Ag-ZnO material of Comparative Example 1, and the thickness of the ablation layer is reduced by ~80%, which proves the excellent performance of the Ag-ZnO material with a network structure according to the present invention in large-rated current low-voltage switch electrical appliances.
[0100] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A silver-oxide contact material comprising silver and oxide, wherein: Based on the total weight of the contact material, the oxide content is 1-20 weight %, and the silver and oxide phases are interconnected, wherein the oxide phase is stacked in one-dimensional and / or two-dimensional asymmetric units to form a continuous skeleton, and the Ag phase is filled in the oxide skeleton to form a structure in which the silver and oxide phases are interconnected.
2. The silver-oxide contact material according to claim 1, wherein The oxides include tin oxide, zinc oxide, and indium oxide.
3. The silver-oxide contact material according to claim 1 or 2, wherein: The content of the oxide is 3-18% based on the total weight of the contact material.
4. The silver-oxide contact material according to claim 1, wherein Based on the total weight of the contact material, the contact material further comprises 0.5-5 wt % of one or more wetting agents selected from copper oxide, lanthanum oxide, tungsten oxide, and bismuth oxide.
5. A method for preparing the silver-oxide contact material according to any one of claims 1 to 4, the method comprising: S1, preparation of oxide asymmetric unit; S2, forming an oxide stacking network structure from the oxide asymmetric unit prepared in step S1; S3, using a melt infiltration method to infiltrate silver into the network structure of the oxide stack to prepare a silver-oxide contact material.
6. The method according to claim 5, wherein: In S1, the oxide asymmetric unit is prepared by flame synthesis, hydrothermal synthesis or electrospinning; and / or In S2, the oxide asymmetric unit prepared in step S1 is subjected to a pressing method, a suction filtration method or a freeze-drying method to form an oxide stacking network structure; and / or In S3, silver is placed on the oxide stacking network structure formed in step S2 or buries the oxide stacking network structure formed in step S2, and the temperature is increased to melt the silver for infiltration.
7. The method according to claim 5 or 6, wherein: In S1, it includes: S1-1, mixing metal Me powder and polyvinyl butyral powder in a mass ratio of 0.05-3:1, and then placing the mixed powder in a furnace preheated to 400-1200° C. in an oxygen-containing environment to burn to produce oxide micrometer wires and / or sheets; or In S1, it includes: S1-1', dissolving the chloride or nitrate of metal Me in a mixed solution of oleic acid and oleamine in a volume ratio of (5-10):1 to achieve a metal Me ion concentration of 0.01-0.5 mol / L, ultrasonicating, oscillating, and stirring until a uniform first solution is obtained; then, a second solution of deionized water and ethanol mixed in a volume ratio of 1:(5-10) equivalent to 40%-50% of the first solution is added dropwise to the first solution, and then the obtained mixed solution is charged into a hydrothermal reactor for hydrothermal reaction to obtain oxide micro / nanowires; or In S1, it includes: S1-1", the chloride or nitrate of metal Me is dissolved in ethanol to obtain a precursor solution A with a concentration of 0.1-0.2 g / mL, polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene oxide or polyvinyl acetate is dissolved in N,N-dimethylformamide to obtain a precursor solution B with a concentration of 0.1-0.2 g / mL, the precursor solutions A and B are ultrasonicated, oscillated and stirred respectively until a uniform solution is obtained; then the precursor solutions A and B are mixed and stirred until uniform, and the mass ratio of precursor solution A: precursor solution B is 0.8-2:1; then the obtained mixed solution is subjected to electrostatic spinning to obtain oxide precursor fibers; the collected oxide precursor fibers are calcined in air at a temperature above 400°C for more than 30 minutes to obtain oxide fibers.
8. The method according to any one of claims 5 to 7, wherein: In S2, the density of the obtained network structure is 2%-30%; and / or If a wetting agent is present, In S2, when a pressing method is used to form an oxide stacking network structure, the oxide asymmetric unit is first pressed into a block, and then the wetting agent is placed on the oxide block or pressed on the oxide block; or the wetting agent and the oxide asymmetric unit are mixed and then pressed together to form the desired oxide stacking network structure; When the network structure of oxide stacking is formed by suction filtration or freeze drying, the wetting agent and the oxide asymmetric unit are dispersed and mixed together with the dispersant, and then the network structure of oxide stacking is formed by suction filtration or freezing.
9. The method according to any one of claims 5 to 8, wherein: In S3, the steps include: embedding the oxide stacking network structure formed in step S2 with silver powder, or making the silver powder into a block, placing the silver block on the oxide stacking network structure formed in S2, and if there is a wetting agent, placing the silver block on the side of the oxide stacking network structure having the wetting agent, heating the silver to melt, and if there is a wetting agent, melting the silver together with the wetting agent to infiltrate the oxide stacking network structure formed in S2; or If the infiltrant is present, S3 includes: embedding the block formed in step S2 with a mixed powder of silver and the infiltrant, or mixing silver powder and the infiltrant powder to form a block, placing the block on the oxide stacking network structure formed in S2, and heating the silver and the infiltrant to melt and penetrate into the oxide stacking network structure formed in S2.
10. The method according to claim 5, wherein: The method comprises: (1) first preparing a zinc oxide network composed of micro / nano wires and sheets: preparing a zinc oxide asymmetric unit by flame synthesis, including mixing zinc powder and polyvinyl butyral powder in a mass ratio of 0.05-3:1, then burning the mixed powder in a furnace at 400-1200° C. in an oxygen-containing environment to produce zinc oxide micro / nano wires and sheets, wherein the zinc powder particle size is 1-500 μm, and molding the obtained zinc oxide micro / nano wires and sheets to obtain a zinc oxide network structure with a density of 2-30%; or dispersing the obtained zinc oxide micro / nano wires and sheets in a solvent, and obtaining a zinc oxide network structure by suction filtration or freeze drying, wherein the solvent is any solvent that does not react with zinc oxide; (2) preparing a silver-zinc oxide contact material containing a zinc oxide micro-nano structure by a melt infiltration method: uniformly covering the top of the zinc oxide network structure with copper oxide powder, pressurizing to form a zinc oxide block with copper oxide covering the top, and pressing silver powder into a block, placing the silver block on the zinc oxide block with copper oxide covering the top, or, mixing silver powder with copper oxide powder and pressing into a block, placing the silver-copper oxide block on the zinc oxide network structure (skeleton), heating in an air environment to a temperature above the silver-copper oxide eutectic point, and preparing a silver-zinc oxide material with a double through-structure by a melt infiltration method, wherein the mass ratio of copper oxide:silver is 0.005-0.05:1, and the mass ratio of zinc oxide:silver is 0.01-0.25:1; Alternatively, the method comprises: (1) First, tin oxide nanowires are prepared: 0.2-1 parts by weight of tin chloride is dissolved in a mixture of oleic acid and oleamine in a volume ratio of (5-10):1 to achieve a metal Sn ion concentration of 0.01-0.5 mol / L, and ultrasonic, oscillated, and stirred for more than 2 hours until a uniform first solution is obtained; then a second solution of deionized water and ethanol mixed in a volume ratio of 1:(5-10) equivalent to 40%-50% of the first solution is added dropwise to the first solution, and then the mixed solution is placed in a hydrothermal reactor and heated at 150-200° C. for 2-10 hours to obtain tin oxide micro / nanowires; the obtained powder and optional bismuth oxide powder are dispersed in a solvent or dispersant, and a tin oxide network structure is obtained by suction filtration or freeze drying; (2) Preparing a silver-tin oxide contact material containing a tin oxide micro-nano structure by a melt infiltration method: placing a silver-bismuth oxide block on a tin oxide network structure, or placing a silver block on a tin oxide network structure containing bismuth oxide in an air environment, heating to a temperature above the silver-bismuth oxide eutectic point, and preparing a silver-tin oxide material with a double-through structure by a melt infiltration method, wherein the mass ratio of bismuth oxide:silver is 0.005-0.05:1, and the mass ratio of tin oxide:silver is 0.01-0.25:1; Alternatively, the method comprises: (1) First, tin oxide nanowires are prepared: stannous chloride is dissolved in ethanol to obtain a precursor solution A with a concentration of 0.1-0.2 g / mL; polyvinyl pyrrolidone, polyvinyl alcohol, polyethylene oxide or polyvinyl acetate is dissolved in N,N-dimethylformamide to obtain a precursor solution B with a concentration of 0.1-0.2 g / mL; liquids A and B are ultrasonically treated, vibrated and stirred for more than 3 hours to obtain a uniform solution; then liquids A and B are mixed and stirred until uniform; the mass ratio of precursor solution A to precursor solution B is 0.8-2:1; then the obtained mixed solution is subjected to electrostatic spinning, wherein the positive electrode voltage is 10-18 kV, the negative electrode voltage is greater than -5 kV, and the distance between the positive and negative electrodes is 10-30 cm, to obtain tin oxide precursor fibers; the collected tin oxide precursor fibers are calcined in air at a temperature above 400° C. for more than 30 minutes to obtain tin oxide fibers; the calcined tin oxide fibers and optional lanthanum oxide powder are dispersed in a solvent or dispersant, and a tin oxide network structure is obtained by suction filtration or freeze drying; (2) Preparing a silver-tin oxide contact material containing a tin oxide micro-nano structure by a melt infiltration method: placing a silver-lanthanum oxide block on a tin oxide skeleton, or placing a silver block on a tin oxide network structure containing lanthanum oxide in an air environment, heating to a temperature above the silver-lanthanum oxide eutectic point, and preparing a silver-tin oxide material with a double-penetrating structure by a melt infiltration method, wherein the mass ratio of lanthanum oxide:silver is 0.005-0.05:1, and the mass ratio of tin oxide:silver is 0.01-0.25:1; Alternatively, the method comprises: (1) First, prepare tin oxide micro / nanowires: put Sn powder into a tube furnace, keep it at 600-1200°C for more than 20 minutes in an oxygen-containing environment, and agglomerate tin oxide nanowires will be generated in the tube furnace; the obtained tin oxide wires are pressed with a mold to obtain a block skeleton with a density of 3-30%; (2) Preparation of silver-tin oxide contact material containing tin oxide micro-nano structure by melt infiltration method: Place a silver-tungsten oxide block on a tin oxide skeleton in an air environment, heat it to a temperature above the silver-tungsten oxide eutectic point, and prepare a silver-tin oxide material with a double-through structure by melt infiltration method, wherein the mass ratio of tungsten oxide:silver is 0.005-0.05:1, and the mass ratio of tin oxide:silver is 0.01-0.25:1.
Citation Information
Patent Citations
Method for preparing silver-based oxide electrical contact material with fibrous structure
CN102031408A